2016
DOI: 10.3390/ijms17122004
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Root Dilatation in Mucopolysaccharidosis I–VII

Abstract: The prevalence of aortic root dilatation (ARD) in mucopolysaccharidosis (MPS) is not well documented. We investigated aortic root measurements in 34 MPS patients at the Children’s Hospital of Orange County (CHOC). The diagnosis, treatment status, age, gender, height, weight and aortic root parameters (aortic valve annulus (AVA), sinuses of Valsalva (SoV), and sinotubular junction (STJ)) were extracted by retrospective chart review and echocardiographic measurements. Descriptive statistics, ANOVA, and paired po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 21 publications
5
25
1
Order By: Relevance
“…In our cohort, there was no significantly higher incidence of ARD at the SoV compared to controls. In contrast, two recent publication reported a higher incidence of ARD in MPS patients, respectively in 39.1% and 35% . However, Poswar et al did not include any MPS III patients in their study, and Bolourchi et al reported the same mean ARD at the SoV in 6 MPS III patients as we report in our patients.…”
Section: Discussioncontrasting
confidence: 79%
See 4 more Smart Citations
“…In our cohort, there was no significantly higher incidence of ARD at the SoV compared to controls. In contrast, two recent publication reported a higher incidence of ARD in MPS patients, respectively in 39.1% and 35% . However, Poswar et al did not include any MPS III patients in their study, and Bolourchi et al reported the same mean ARD at the SoV in 6 MPS III patients as we report in our patients.…”
Section: Discussioncontrasting
confidence: 79%
“…While CD was previously not considered to be present in MPS III, several recent studies reported cardiac involvement . In addition, CD may also be related to sudden unexpected death reported in some patients …”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations